2016
DOI: 10.1099/mic.0.000327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of differing +2 amino acids on export of a heterologous PhoA lipoprotein in Mycoplasma gallisepticum

Abstract: The significance of the amino acid adjacent to the amino terminal cysteine of lipoproteins, the +2 amino acid, has been well documented in E. coli and there have also been limited studies on Gram-positive bacteria. In this study we investigated whether there was any preference for specific residues and any targeting role attributable to different residues following the cysteine at the amino terminus in lipoproteins of Mycoplasma gallisepticum. There were found to be distinct preferences in this position that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In P. aeruginosa Lpp that are located in the inner membrane have Gly+2 followed by Asp/Glu +3 (Remans, Vercammen, Bodilis, & Cornelis, 2010). Recently, it has been shown that aa variations in +2 of the alkaline phosphatase (PhoA) expressed in Mycoplasma gallisepticum did not affect the retention of PhoA to the membrane (Panicker, Kanci, Markham, & Browning, 2016). Finally, in Bacillus subtilis it was found that Gly+2 facilitates release of Lpp while a Ser+2 favors withholding in the membrane (Tjalsma & van Dijl, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In P. aeruginosa Lpp that are located in the inner membrane have Gly+2 followed by Asp/Glu +3 (Remans, Vercammen, Bodilis, & Cornelis, 2010). Recently, it has been shown that aa variations in +2 of the alkaline phosphatase (PhoA) expressed in Mycoplasma gallisepticum did not affect the retention of PhoA to the membrane (Panicker, Kanci, Markham, & Browning, 2016). Finally, in Bacillus subtilis it was found that Gly+2 facilitates release of Lpp while a Ser+2 favors withholding in the membrane (Tjalsma & van Dijl, 2005).…”
Section: Discussionmentioning
confidence: 99%